The Role of Perceived Employability In The Relationship Self-Efficacy and Subjective Career Success - Tika Rahma Yani Siregar; Bulan Nettiary Kelara (Trunojoyo University of Madura, 2026)
Purpose: This study aims to examine the effect of self-efficacy on subjective career success among employees of Islamic tourisme companies. In addition, the study investigates the mediating role of perceived employability, specifically internal and external employability, in explaining the relationship between self-efficacy and subjective career success.Design/methodology/approach: This research employed a quantitative approach using a causal research design. Data were collected through questionnaires distributed to employees working in Islamic Tourisme companies in West Sumatra, Indonesia. A total of 200 valid responses were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0.Findings: The findings reveal that self-efficacy does not directly influence subjective career success. However, self-efficacy significantly affects both perceived internal employability and perceived external employability. Furthermore, internal and external employability significantly influence subjective career success and fully mediate the relationship between self-efficacy and subjective career success. These results indicate that employability perceptions play an essential role in transforming employees’ confidence into positive career outcomes.Research limitations/implications: This study is limited to employees in the Islamic tourism sector and uses a cross-sectional design. Future research is recommended to apply longitudinal approaches and examine broader industrial contexts.Practical implications: Organizations should strengthen employees’ self-efficacy and employability through career development programs, training, and competency enhancement initiatives to improve career success outcomes.Originality/value: This study contributes to the career development literature by simultaneously examining perceived internal and external employability as mediating variables in the relationship between self-efficacy and subjective career success within the Islamic tourism industry context.